Perilaku Bullying Pada Mahasiswa: Menelisik Pengaruh Harga Diri dan Konformitas (SUKMA : Jurnal Penelitian Psikologi, 2020)
Bullying behavior that has been synonymous with teenagers, apparently also carried out by many students. It is interesting to study what factors are the causes of high bullying behavior in students, whether internal factors or external factors. The purpose of this study is to examine the relationship between self-esteem and conformity with bullying behavior in students. Participants in this study were 114 students taken using the Disproportional Stratified Random Sampling technique. Research data were collected through self-esteem scale (? = .831), conformity scale (? = .831) and bullying behavior scale (? = .831). The results of data analysis using Spearman’s Rho correlation show there is a negative correlation between self-esteem and bullying behavior in college students. An interesting finding from this research is the absence of a correlation between conformity and bullying behavior in students. Keywords: Bullying behavior; Conformity;  Self-esteem    Abstrak Perilaku bullying yang selama ini identik dengan remaja, ternyata juga banyak dilakukan oleh Mahasiswa. Menarik untuk diteliti faktor apa yang menjadi penyebab tingginya perilaku bullying pada mahasiswa, apakah faktor internal ataukah faktor eksternal yang lebih dominan. Tujuan penelitian ini adalah untuk menguji hubungan antara harga diri dan konformitas dengan perilaku bullying pada mahasiswa.  Partisipan dalam penelitian ini berjumlah 114 mahasiswa yang diambil menggunakan teknik Disproportional Stratified Random Sampling. Data penelitian dikumpulkan melalui skala harga diri (? = .831), skala konformitas (? = .831) dan skala perilaku bullying (? = .831). Hasil analisis data menggunakan korelasi Spearman’s Rho menunjukkan ada korelasi negatif antara harga diri dengan perilaku bullying pada mahasiswa. Temuan menarik dari penelitian ini adalah tidak adanya korelasi antara konformitas dengan perilaku bullying pada mahasiswa. Kata kunci : Harga diri; Konformitas; Perilaku bullying